Tourism inflow interlinkages with merchandise exports: An augmented gravity analysis for the Pacific - Pralok Gupta; Sanchita Basu Das; Saarthak Sharma; Ma. Veronica Domingo (Asian Development Bank (ADB), 2024)
Pacific developing member countries (DMCs) depend heavily on international tourism, which can promote merchandise exports by reducing trade costs. This paper empirically analyzes tourist inflows as a determinant of merchandise exports for Pacific DMCs by deploying a gravity model technique. Other relevant variables that augment the model are trade agreements, language affinity, visa policies, etc. The paper finds that inbound tourism to Pacific DMCs significantly increases merchandise exports: a 1% increase in tourist inflows is associated with a 0.17% rise in merchandise exports in the region. This relationship is along expected lines, as international tourist arrivals can help reduce trade costs, increasing such exports. If international tourists come from countries with a shared language and that have formed an economic partnership through free trade agreements and easy visa policies, the increase is bigger. Based on the findings, the paper recommends that inbound tourism be used to develop other industries such as garments or souvenir-related manufacturing in countries in the region. These products hold good export potential, provided they can be customized to the tastes and preferences of international tourists.
Keywords: C33; F14; L83; Z38; 330; tourism; international trade; Pacific developing member countries